2020
DOI: 10.1111/liv.14432
|View full text |Cite
|
Sign up to set email alerts
|

Liver enzyme variability and risk of heart disease and mortality: A nationwide population‐based study

Abstract: Background & Aims:Liver enzymes, such as alanine aminotransferase (ALT), aspartate aminotransferase (AST) and γ-glutamyltransferase (GGT), have been suggested as surrogate markers of various cardiovascular diseases. However, previous studies assessed liver enzymes only once at baseline. We investigated the association between liver enzyme variability and the risk of mortality and cardiovascular outcomes in general population. Methods:A total of 6 496 271 subjects participating in ≥3 health examinations within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
4
16
0
2
Order By: Relevance
“…In a recent nationwide population-based study in Korea, higher variability in AST, ALT, and γ-glutamyltransferase levels was associated with a higher risk for all-cause mortality, myocardial infarction, atrial fibrillation, and congestive heart failure. In addition, these findings were consistent regardless of baseline characteristics including alco-hol consumption, BMI, and degree of fatty liver [22]. However, to our best knowledge, our current study is the first report to determine the association between visit-to-visit liver enzyme variability and diabetes risk independent of traditional risk factors of diabetes and mean levels.…”
Section: Discussionsupporting
confidence: 76%
“…In a recent nationwide population-based study in Korea, higher variability in AST, ALT, and γ-glutamyltransferase levels was associated with a higher risk for all-cause mortality, myocardial infarction, atrial fibrillation, and congestive heart failure. In addition, these findings were consistent regardless of baseline characteristics including alco-hol consumption, BMI, and degree of fatty liver [22]. However, to our best knowledge, our current study is the first report to determine the association between visit-to-visit liver enzyme variability and diabetes risk independent of traditional risk factors of diabetes and mean levels.…”
Section: Discussionsupporting
confidence: 76%
“…Even though TBil is not an independent risk factor for valvular AF recurrence in the multivariate analysis, we found that the AUC area increased after adding TBil variable to the model(model1 AUC 0.720 versus model3 AUC 0.679) which indicating that there may becomes more statistically significant differences between TBil and valvular AF recurrence in larger cohorts. In addition, liver injury parameters (ALT, AST, GGT), mainly GGT, has been considered as a significantly risk factor of cardiovascular diseases, including myocardial infarction, stroke and atrial fibrillation(AF) 32,[35][36][37] . Although GGT level is reasonable to assume related to the elevated occurrence of AF in previous studies, we found no statistically difference in AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…And besides liver function, AST was also used to evaluate myocaridium damage. Some reports indicated that higher visit-to-visit variability of liver enzymes was an independent predictor of all-cause mortality and cardiovascular events [30,31]. From the analysis mentioned above, acute cardiac injury would appear in about 59% patients in nonsurvivors' group compared to 1% in survivors', and usually happened 15 days after admission with acute elevation of hsTnI [7].…”
Section: Discussionmentioning
confidence: 99%